Teori Hasrat Peniruan pada Kegiatan Membaca di Perpustakaan Sekolah Dasar Kabupaten Sidoarjo - Kuswanto Kuswanto; Hardono Hardono (Journal on Education, 2023)
Why do elementary school students in Sidoarjo tend to have changeable behavior in terms of reading and borrowing books in the school library? This paper describes the mimetic mechanism of Rene Girard in activities in the library, namely borrowing books and reading with the teacher. Data was collected by reading the 2019-2020 Quarterly Report, especially data on borrowing books from 10 elementary schools for 6 months, selecting 2 photos of reading aloud activities, and interviewing 5 teacher informants. Specifically, in interviews, the 5 informants were included in a joint evaluation meeting with 120 participants first, then were interviewed in depth separately. The three types of data were analyzed based on 4 themes derived from the theory of Mimetic Desire with a mixed approach (mixed method research). Data validation was analyzed by triangulation of data sources and triangulation of methods. The findings in this study provide a thematic description based on Rene Girard's Mimetic Desire theory that elementary school students in Sidoarjo tend to have behavior that changes according to the mimetic mechanism in reading and borrowing books in the library.